Engineering Fundamentals, 6th Edition - Saeed Moaveni (Cengage Learning, 2019)
Discover what it takes to be a successful engineer today with Moaveni's ENGINEERING FUNDAMENTALS: AN INTRODUCTION TO ENGINEERING, SI Edition, 6th Edition. This reader-friendly approach helps you develop the strong problem-solving skills and solid foundation in fundamental principles you need to become an analytical, detail-oriented and creative engineer. This edition opens with an overview of what engineers do and includes behind-the-scenes glimpses inside areas of specialization. Candid, straight-forward discussions examine what you need to succeed as an engineer today. You study basic physical concepts and laws that are important in your engineering studies as well as on the job. In addition, Professional Profiles throughout this edition highlight the work of practicing engineers around the globe and connect the fundamental principles you're learning to professional engineering success.